Composite wire for bending-resistant medical wire and preparation method thereof

By spraying the composite coating prepared from specific raw materials on the surface of the copper wire and wrapping it in the modified basalt fiber wire, the problem of poor bending and corrosion resistance of composite wires is solved, and high reliability and safety are achieved. Medical wires.

CN119410220AActive Publication Date: 2025-02-11DONGGUAN LINGKANG CABLE CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411538032.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The bending and corrosion resistance of existing composite wires is poor, making it difficult to meet the reliability and safety requirements of medical wires in frequent bending and torsional environments.

Method used

The composite coating prepared from 3,8-dibromophenanthroline, 4-carboxylic acid, fullerene and polyvinylpyrrolidone were sprayed on the surface of the copper wire, and the metal round copper wire was tightly wrapped in the modified basalt fiber wire. On the surface, the prepared composite wire has excellent bending resistance and corrosion resistance.

Benefits of technology

The excellent bending and corrosion resistance of composite wires are achieved, and the reliability and safety of medical wires in complex environments are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410220A_ABST
    Figure CN119410220A_ABST
Patent Text Reader

Abstract

The invention discloses a composite wire for a bending-resistant medical wire and a preparation method thereof, and belongs to the technical field of preparation of composite wires. The composite wire for the bending-resistant medical wire is composed of a central fiber and a metal round copper wire, the metal round copper wire tightly wraps the surface of the central fiber, the metal round copper wire is prepared from a metal copper wire and a composite coating, and the composite coating is prepared from 3, 8-dibromophenanthroline, 4-formylphenylboronic acid, fullerene and sarcosine. The central fiber yarn is prepared from modified basalt fiber, 4, 4 '-dihydroxybenzophenone and 1, 4-bis (4-fluorobenzoyl) benzene, and the composite wire prepared by the method has excellent bending resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite wire preparation, and in particular relates to a composite wire for bending-resistant medical electric wire and a preparation method thereof. Background Art

[0002] In the modern medical field, with the popularization of minimally invasive surgery and the continuous advancement of medical equipment, the performance requirements for medical wires are also increasing. Especially in medical environments that require frequent bending and twisting, traditional metal wires are often difficult to meet the needs. Therefore, the research on composite wires for bending-resistant medical wires came into being, aiming to solve the problems of traditional wires being easy to break during bending and unstable signal transmission, and to improve the reliability and safety of medical equipment.

[0003] Bend-resistant medical wires play an important role in many fields. For example, in implantable medical devices such as pacemakers and neurostimulators, the wires need to work in the patient's body for a long time and withstand the influence of various physiological activities and external forces. If the wire does not have sufficient bending resistance, it is easy to break during implantation or use, resulting in device failure and even secondary injury to the patient. In addition, in in vitro medical devices such as endoscopes and surgical robots, the wires also need to be bent and twisted frequently to adapt to complex surgical environments and operational requirements. Therefore, the development of composite wires with excellent bending resistance is of great significance to improving the reliability and safety of medical equipment.

[0004] Patent CN207676687U discloses a medical composite cable, which includes a coaxial line and a conductor, wherein a plurality of the conductors are arranged around the coaxial line, and the plurality of conductors are wrapped with aluminum foil, and the aluminum foil is covered with braiding, and the outer surface of the braiding is covered with an outer sheath; the circumferential side of the conductor is covered with an insulating layer; the gap between the insulating layer and the coaxial line is filled with a filling wire, the conductor is made of twisted tinned copper wire, and the braiding is made of tinned copper wire. The coaxial line is shielded by aluminum foil and copper mesh, and the wire has the advantages of high data transmission efficiency and strong shielding and anti-interference performance, and can also prevent water and oxygen erosion. However, the bending resistance and corrosion resistance of the cable prepared by this method still have room for improvement. Summary of the invention

[0005] The object of the present invention is to provide a composite conductor for a bending-resistant medical wire and a preparation method thereof, so as to solve the technical problem that the composite conductor in the prior art has poor bending resistance and corrosion resistance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention provides a composite wire for bending-resistant medical wires. The composite wire is composed of a central fiber and a metal round copper wire, wherein the metal round copper wire is tightly wrapped on the surface of the central fiber. The metal round copper wire is prepared from a metal copper wire and a composite coating, and the composite coating is prepared from 3,8-dibromophenanthroline, 4-formylphenylboric acid, fullerene and sarcosine. The central fiber is prepared from modified basalt fiber, 4,4'-dihydroxybenzophenone and 1,4-bis(4-fluorobenzoyl)benzene. The outer diameter of the composite wire is 0.02-0.10 mm, and the number of strands is 1-12.

[0008] Preferably, the method for preparing the composite coating comprises the following steps:

[0009] Q1: Add 3,8-dibromophenanthroline, sodium carbonate and 4-formylphenylboronic acid to a container containing N,N-dimethylformamide, stir evenly, then add 1,4-dioxane, ethanol, methyltrioctylammonium chloride and tetrakis(triphenylphosphine)palladium, degas with nitrogen, heat and stir to react, after the reaction is completed, cool to room temperature, add chloroform to dissolve the product, wash, separate and collect the organic phase, dry, filter, concentrate and purify to obtain intermediate 1;

[0010] Q2: Add intermediate 1, fullerene and sarcosine into a container, then add chlorobenzene and heat to react. After the reaction is completed, perform vacuum distillation and purification to obtain intermediate 2, which is then mixed with polyvinyl pyrrolidone and distilled water to obtain a composite coating.

[0011] In the above process, 3,8-dibromophenanthroline and 4-formylphenylboronic acid are first used as raw materials to obtain intermediate 1 through reaction, and then intermediate 1 is mixed with fullerene to undergo a pratol reaction to obtain intermediate 2. Intermediate 2, polyvinyl pyrrolidone and distilled water are then mixed to obtain a composite coating, wherein the synthesis reaction formula of intermediate 1 is as follows:

[0012]

[0013] The results of mass spectrometry analysis were: m / z: 388.12 (100.0%), 389.12 (28.9%), 390.13 (4.3%).

[0014] Preferably, in Q1, the dosage ratio of 3,8-dibromophenanthroline, sodium carbonate, 4-formylphenylboric acid, N,N-dimethylformamide, 1,4-dioxane, ethanol, methyltrioctylammonium chloride and tetrakis(triphenylphosphine)palladium is (0.033-0.066) g: (0.105-0.21) g: (0.051-0.1) g: (4-8) mL: (3-6) mL: (0.4-0.8) mL: (0.033-0.067) mL: (0.05-0.1) mL, the nitrogen degassing time is 30-45 min, the heating and stirring temperature is 110-120° C., the reaction time is 3-5 h, the product is washed with saturated sodium carbonate and distilled water, dried with anhydrous sodium sulfate, and purified with a mixed solution of chloroform and ethyl acetate in a volume ratio of 7:1 as an eluent.

[0015] Preferably, in Q2, the amount ratio of intermediate 1, fullerene, sarcosine and chlorobenzene is (8.6-17.3) mg: (40-80) mg: (22-44.84) ​​mg: (10-20) mL, the heating reaction temperature is 110-120°C, the time is 10-12 h, and the purification is carried out using a mixed solution of carbon disulfide and ethyl acetate in a volume ratio of 20:1 as an eluent, the amount ratio of intermediate 2, polyvinyl pyrrolidone and distilled water is (10-20) g: (2-7) g: (8-12) mL, and the mixing and stirring time is 2-4 h.

[0016] Preferably, the method for preparing the central fiber yarn comprises the following steps:

[0017] S1: heat-treating the basalt fiber, cooling it after the treatment, heating it in a hydrochloric acid solution for pickling, filtering, washing, and drying it to obtain pretreated basalt fiber, mixing deionized water and hexadecyltrimethylammonium bromide, heating and stirring, adding the pretreated basalt fiber, soaking it, washing it, and drying it to obtain modified fiber 1;

[0018] S2: adding silane coupling agent KH-602 to the ethanol solution, heating and stirring, then adding modified fiber 1, soaking, filtering, washing, and drying to obtain modified basalt fiber;

[0019] S3: Add diphenyl sulfone to a container, and then add 4,4'-dihydroxybenzophenone, 1,4-bis(4-fluorobenzoyl)benzene and sodium carbonate in sequence after heating, and heat to react. After the reaction is completed, cool, crush, wash, and vacuum dry to obtain a powder;

[0020] S4: After the powder and modified basalt fiber are evenly mixed, they are added into a twin-screw extruder, extruded after melting, and stretched to obtain a central fiber filament.

[0021] In the above process, the basalt fiber is firstly heated to remove moisture and impurities, then pickled to regenerate the hydroxyl groups on its surface, and then compounded and modified with hexadecyltrimethylammonium bromide and silane coupling agent KH-602 to obtain modified basalt fiber, and then diphenyl sulfone is used as solvent, 4,4'-dihydroxybenzophenone and 1,4-bis(4-fluorobenzoyl)benzene are used as raw materials to react under high temperature environment to obtain powder, and then the modified basalt fiber is mixed with the powder to prepare the central fiber.

[0022] Preferably, in S1, the heating treatment temperature is 500-550°C, the concentration of the hydrochloric acid solution is 1 mol / L, the heating pickling temperature is 80-90°C, the time is 5-7h, the fiber is washed with deionized water until pH=7, the drying temperature is 70-80°C, the time is 10-12h, the amount ratio of deionized water, hexadecyltrimethylammonium bromide and pretreated basalt fiber is (150-300)mL: (1-2)g: (10-20)g, the mixing temperature is 60-70°C, the time is 30-45min, the soaking time is 6-8h, the fiber is washed with deionized water, the drying temperature is 70-85°C, and the time is 10-12h.

[0023] Preferably, in S2, the volume fraction of the ethanol solution is 90vt%, the usage ratio of the ethanol solution, the silane coupling agent KH-602 and the modified fiber 1 is (100-120)mL:(6-7.2)g:(10-12)g, the heating and stirring temperature is 60-80°C, the time is 30-45min, the soaking time is 10-12h, the washing is carried out with anhydrous ethanol, the drying temperature is 80-90°C, and the time is 10-12h.

[0024] Preferably, in S3, the dosage ratio of diphenyl sulfone, 4,4'-dihydroxybenzophenone, 1,4-bis(4-fluorobenzoyl)benzene and sodium carbonate is (240-360) mL: (32-48) g: (49-74) g: (19-29) g, the heating temperature is 160-170°C, and the heating reaction process is: first heating to 220°C, maintaining for 1 hour, then heating to 320°C, stirring continuously for 3 hours, washing with acetone and distilled water, and vacuum drying at 80-85°C for 10-12 hours; in S4, the mass ratio of powder to modified basalt fiber is (10-20): (30-50).

[0025] Preferably, the method for preparing the composite conductor for bending-resistant medical wire comprises the following steps:

[0026] Step (1): spraying the prepared composite coating evenly on the surface of the copper wire, and drying to obtain a metal round copper wire;

[0027] Step (2): Wrap the metal round copper wire tightly on the surface of the central fiber wire and compact it to obtain a composite conductor for bending-resistant medical wire with an outer diameter of 0.02 to 0.10 mm and a strand number of 1 to 12.

[0028] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0029] 1. The present invention first uses 3,8-dibromophenanthroline, 4-formylphenylboric acid, fullerene and polyvinylpyrrolidone as raw materials to prepare a composite coating, then uses basalt fiber, hexadecyltrimethylammonium bromide, silane coupling agent KH-602, 4,4'-dihydroxybenzophenone and 1,4-bis(4-fluorobenzoyl)benzene as raw materials to prepare a central fiber, sprays the composite coating onto the surface of the copper wire to obtain a metal round copper wire, and then wraps the metal round copper wire on the surface of the central fiber to prepare a composite conductor for bending-resistant medical wires. The composite conductor prepared by the method has excellent bending resistance and corrosion resistance.

[0030] 2. The present invention uses 3,8-dibromophenanthroline, 4-formylphenylboronic acid, fullerene and polyvinylpyrrolidone as raw materials to prepare a composite coating. Spraying of the composite coating can effectively improve the corrosion resistance and electrical conductivity of the metal round copper wire. The fullerene in the composite coating, as a carbon material with a special cage structure, can form a solid barrier layer on the surface of the copper wire, and 3,8-dibromophenanthroline and 4-formylphenylboronic acid can be tightly combined with the surface of the copper wire to form a dense protective film. The presence of the protective film can isolate the corrosive medium in the external environment from direct contact with the copper wire, thereby improving the corrosion resistance of the copper wire. Fullerene is a carbon material with excellent electrical conductivity. It is evenly distributed in the coating and can form a conductive network on the surface of the copper wire, thereby improving the electrical conductivity of the coating, reducing resistance, and improving current transmission efficiency.

[0031] 3. The present invention uses basalt fiber, hexadecyltrimethylammonium bromide, silane coupling agent KH-602, 4,4'-dihydroxybenzophenone and 1,4-bis(4-fluorobenzoyl)benzene as raw materials to prepare central fiber yarns. The introduction of silane coupling agent KH-602 can improve the interfacial bonding force between the modified basalt fiber and the powder. The enhancement of the interfacial bonding force makes it difficult for the central fiber yarn to be pulled out or fall off from the matrix when subjected to external force, so that the central fiber yarn can better disperse and transfer stress when subjected to bending force, thereby improving the bending resistance of the composite conductor. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is a schematic structural diagram of the composite conductor for bending-resistant medical wire in the present invention.

[0034] Description of the drawings: 1. Metal round copper wire, 2. Central fiber wire. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1: See Figure 1 In this embodiment, the composite conductor is composed of a metal round copper wire 1 and a central fiber wire 2, and the metal round copper wire is tightly wrapped around the surface of the central fiber wire.

[0037] This embodiment discloses a method for preparing a composite coating, comprising the following steps:

[0038] Q1: Add 0.05 g 3,8-dibromophenanthroline, 0.15 g sodium carbonate and 0.075 g 4-formylphenylboronic acid to a container containing 6 mL N,N-dimethylformamide, stir evenly, then add 4.5 mL 1,4-dioxane, 0.6 mL ethanol, 0.05 mL methyltrioctylammonium chloride and 0.07 mL tetrakis(triphenylphosphine)palladium, degas with nitrogen for 45 min, heat and stir at 110 °C for 5 h, after the reaction is completed, cool to room temperature, add chloroform to dissolve the product, wash with saturated sodium carbonate and distilled water, separate and collect the organic phase, dry with anhydrous sodium sulfate, filter and concentrate, purify with a mixed solution of chloroform and ethyl acetate in a volume ratio of 7:1 as the eluent to obtain intermediate 1;

[0039] Q2: 12.5 mg of intermediate 1, 60 mg of fullerene and 33.42 mg of sarcosine were added to a container, followed by 15 mL of chlorobenzene. The mixture was heated at 120°C for 12 h. After the reaction was completed, it was distilled under reduced pressure and purified using a mixed solution of carbon disulfide and ethyl acetate in a volume ratio of 20:1 as an eluent. After purification, intermediate 2 was obtained. 15 g of intermediate 2 was mixed with 4.5 g of polyvinyl pyrrolidone and 10 mL of distilled water and stirred for 3 h to obtain a composite coating.

[0040] This embodiment discloses a method for preparing a central fiber, comprising the following steps:

[0041] S1: The basalt fiber was subjected to a heating treatment at 550°C. After the treatment, the fiber was cooled, placed in a 1 mol / L hydrochloric acid solution and heated at 80°C for pickling for 6 h, filtered, washed with deionized water until pH = 7, and dried at 80°C for 12 h to obtain pretreated basalt fiber. 225 mL of deionized water and 1.5 g of hexadecyltrimethylammonium bromide were mixed at 60°C for 45 min, heated and stirred, 15 g of pretreated basalt fiber was added, and the fiber was soaked for 7 h, washed with deionized water, and dried at 70°C for 12 h to obtain modified fiber 1.

[0042] S2: Add 6.6 g of silane coupling agent KH-602 to 110 mL of 90 vt% ethanol solution, heat to 60 ° C and stir for 45 min, then add 11 g of modified fiber 1, soak for 12 h, filter, wash with anhydrous ethanol, and dry at 80 ° C for 10 h to obtain modified basalt fiber;

[0043] S3: Add 300 mL of diphenyl sulfone to a container, heat to 170°C, then add 40 g of 4,4'-dihydroxybenzophenone, 61 g of 1,4-bis(4-fluorobenzoyl)benzene and 24 g of sodium carbonate in sequence, and heat to react. The reaction process is: first heat to 220°C, maintain for 1 hour, then heat to 320°C, and continue stirring for 3 hours. After the reaction is completed, cool, crush, wash with acetone and distilled water, and vacuum dry at 85°C for 12 hours to obtain a powder;

[0044] S4: 15 g of powder and 40 g of modified basalt fiber are mixed evenly, added into a twin-screw extruder, extruded after melting, and stretched to obtain a central fiber filament.

[0045] This embodiment discloses a method for preparing a composite conductor for bending-resistant medical wire, comprising the following steps:

[0046] Step (1): spraying the prepared composite coating evenly on the surface of the copper wire, and drying to obtain a metal round copper wire;

[0047] Step (2): Wrap the metal round copper wire tightly on the surface of the central fiber wire and compact it to obtain a composite conductor for bending-resistant medical wire with an outer diameter of 0.06 mm and 7 strands.

[0048] Embodiment 2: This embodiment discloses a method for preparing a composite coating, comprising the following steps:

[0049] Q1: 0.033 g 3,8-dibromophenanthroline, 0.105 g sodium carbonate and 0.1 g 4-formylphenylboronic acid were added to a container containing 4 mL N,N-dimethylformamide, and stirred evenly. Then, 3 mL 1,4-dioxane, 0.8 mL ethanol, 0.067 mL methyltrioctylammonium chloride and 0.05 mL tetrakis(triphenylphosphine)palladium were added, and nitrogen was degassed for 45 min. The mixture was heated and stirred at 110°C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, chloroform was added to dissolve the product, and the product was washed with saturated sodium carbonate and distilled water. The organic phase was separated and collected, dried with anhydrous sodium sulfate, filtered and concentrated, and purified with a mixed solution of chloroform and ethyl acetate in a volume ratio of 7:1 as the eluent to obtain intermediate 1;

[0050] Q2: 8.6 mg of intermediate 1, 40 mg of fullerene and 44.84 mg of sarcosine were added to a container, followed by 10 mL of chlorobenzene. The mixture was heated at 120°C for 12 h. After the reaction was completed, it was distilled under reduced pressure and purified using a mixed solution of carbon disulfide and ethyl acetate in a volume ratio of 20:1 as an eluent. After purification, intermediate 2 was obtained. 10 g of intermediate 2 was mixed with 7 g of polyvinyl pyrrolidone and 8 mL of distilled water and stirred for 3 h to obtain a composite coating.

[0051] This embodiment discloses a method for preparing a central fiber, comprising the following steps:

[0052] S1: The basalt fiber was subjected to a heating treatment at 550°C. After the treatment, the fiber was cooled, placed in a 1 mol / L hydrochloric acid solution and heated at 80°C for pickling for 6 h, filtered, washed with deionized water until pH = 7, and dried at 80°C for 12 h to obtain a pretreated basalt fiber. 150 mL of deionized water and 1 g of hexadecyltrimethylammonium bromide were mixed at 60°C for 45 min, heated and stirred, 20 g of the pretreated basalt fiber was added, and the fiber was soaked for 7 h, washed with deionized water, and dried at 70°C for 12 h to obtain a modified fiber 1.

[0053] S2: Add 7.2 g of silane coupling agent KH-602 to 100 mL of 90% by volume ethanol solution, heat to 60°C and stir for 45 min, then add 10 g of modified fiber 1, soak for 12 h, filter, wash with anhydrous ethanol, and dry at 80°C for 10 h to obtain modified basalt fiber;

[0054] S3: Add 240 mL of diphenyl sulfone to a container, heat to 170°C, then add 32 g of 4,4'-dihydroxybenzophenone, 49 g of 1,4-bis(4-fluorobenzoyl)benzene and 29 g of sodium carbonate in sequence, and heat to react. The reaction process is: first heat to 220°C, maintain for 1 hour, then heat to 320°C, and continue stirring for 3 hours. After the reaction is completed, cool, crush, wash with acetone and distilled water, and vacuum dry at 85°C for 12 hours to obtain a powder;

[0055] S4: 10 g of powder and 50 g of modified basalt fiber are mixed evenly, added into a twin-screw extruder, extruded after melting, and stretched to obtain a central fiber filament.

[0056] This embodiment discloses a method for preparing a composite conductor for bending-resistant medical wire, comprising the following steps:

[0057] Step (1): spraying the prepared composite coating evenly on the surface of the copper wire, and drying to obtain a metal round copper wire;

[0058] Step (2): Wrap the metal round copper wire tightly on the surface of the central fiber wire and compact it to obtain a composite conductor for bending-resistant medical wire with an outer diameter of 0.08 mm and 9 strands.

[0059] Embodiment 3: This embodiment discloses a method for preparing a composite coating, comprising the following steps:

[0060] Q1: 0.066 g 3,8-dibromophenanthroline, 0.21 g sodium carbonate and 0.051 g 4-formylphenylboronic acid were added to a container containing 8 mL N,N-dimethylformamide, and stirred evenly. Then, 6 mL 1,4-dioxane, 0.4 mL ethanol, 0.033 mL methyltrioctylammonium chloride and 0.1 mL tetrakis(triphenylphosphine)palladium were added, and nitrogen was degassed for 45 min. The mixture was heated and stirred at 110°C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, chloroform was added to dissolve the product, and the product was washed with saturated sodium carbonate and distilled water. The organic phase was separated and collected, dried with anhydrous sodium sulfate, filtered and concentrated, and purified with a mixed solution of chloroform and ethyl acetate in a volume ratio of 7:1 as the eluent to obtain intermediate 1;

[0061] Q2: 17.3 mg of intermediate 1, 80 mg of fullerene and 22 mg of sarcosine were added to a container, followed by 20 mL of chlorobenzene. The mixture was heated at 120°C for 12 h. After the reaction was completed, it was distilled under reduced pressure and purified using a mixed solution of carbon disulfide and ethyl acetate in a volume ratio of 20:1 as an eluent. After purification, intermediate 2 was obtained. 20 g of intermediate 2 was mixed with 2 g of polyvinyl pyrrolidone and 12 mL of distilled water and stirred for 3 h to obtain a composite coating.

[0062] This embodiment discloses a method for preparing a central fiber, comprising the following steps:

[0063] S1: The basalt fiber was subjected to a heating treatment at 550°C. After the treatment, the fiber was cooled, placed in a hydrochloric acid solution with a concentration of 1 mol / L and heated at 80°C for pickling for 6 h, filtered, washed with deionized water until pH = 7, and dried at 80°C for 12 h to obtain a pretreated basalt fiber. 300 mL of deionized water and 2 g of hexadecyltrimethylammonium bromide were mixed at 60°C for 45 min, heated and stirred, 10 g of the pretreated basalt fiber was added, and the fiber was soaked for 7 h, washed with deionized water, and dried at 70°C for 12 h to obtain a modified fiber 1.

[0064] S2: Add 6 g of silane coupling agent KH-602 to 120 mL of 90 vt% ethanol solution, heat at 60 ° C and stir for 45 min, then add 12 g of modified fiber 1, soak for 12 h, filter, wash with anhydrous ethanol, and dry at 80 ° C for 10 h to obtain modified basalt fiber;

[0065] S3: Add 360 mL of diphenyl sulfone to a container, heat to 170°C, then add 48 g of 4,4'-dihydroxybenzophenone, 74 g of 1,4-bis(4-fluorobenzoyl)benzene and 19 g of sodium carbonate in sequence, and heat to react. The reaction process is: first heat to 220°C, maintain for 1 hour, then heat to 320°C, and continue stirring for 3 hours. After the reaction is completed, cool, crush, wash with acetone and distilled water, and vacuum dry at 85°C for 12 hours to obtain a powder;

[0066] S4: 20 g of powder and 30 g of modified basalt fiber are mixed evenly, added into a twin-screw extruder, extruded after melting, and stretched to obtain a central fiber filament.

[0067] This embodiment discloses a method for preparing a composite conductor for bending-resistant medical wire, comprising the following steps:

[0068] Step (1): spraying the prepared composite coating evenly on the surface of the copper wire, and drying to obtain a metal round copper wire;

[0069] Step (2): Wrap the metal round copper wire tightly on the surface of the central fiber wire and compact it to obtain a composite conductor for bending-resistant medical wire with an outer diameter of 0.09 mm and 10 strands.

[0070] Embodiment 4: This embodiment discloses a method for preparing a composite coating, comprising the following steps:

[0071] Q1: 0.044 g 3,8-dibromophenanthroline, 0.19 g sodium carbonate and 0.063 g 4-formylphenylboronic acid were added to a container containing 5 mL N,N-dimethylformamide, and stirred evenly. Then, 4 mL 1,4-dioxane, 0.5 mL ethanol, 0.042 mL methyltrioctylammonium chloride and 0.06 mL tetrakis(triphenylphosphine)palladium were added, and nitrogen was degassed for 45 min. The mixture was heated and stirred at 110°C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, chloroform was added to dissolve the product, and the product was washed with saturated sodium carbonate and distilled water. The organic phase was separated and collected, dried with anhydrous sodium sulfate, filtered and concentrated, and purified with a mixed solution of chloroform and ethyl acetate in a volume ratio of 7:1 as the eluent to obtain intermediate 1;

[0072] Q2: 10.4 mg of intermediate 1, 50 mg of fullerene and 27.15 mg of sarcosine were added to a container, followed by 12 mL of chlorobenzene. The mixture was heated at 120°C for 12 h. After the reaction was completed, it was distilled under reduced pressure and purified using a mixed solution of carbon disulfide and ethyl acetate in a volume ratio of 20:1 as an eluent. After purification, intermediate 2 was obtained. 12 g of intermediate 2 was mixed with 3 g of polyvinyl pyrrolidone and 11 mL of distilled water and stirred for 3 h to obtain a composite coating.

[0073] This embodiment discloses a method for preparing a central fiber, comprising the following steps:

[0074] S1: The basalt fiber was subjected to a heating treatment at 550°C. After the treatment, the fiber was cooled, placed in a 1 mol / L hydrochloric acid solution and heated at 80°C for 6 h for acid washing, filtered, washed with deionized water until pH = 7, and dried at 80°C for 12 h to obtain a pretreated basalt fiber. 200 mL of deionized water and 1.2 g of hexadecyltrimethylammonium bromide were mixed at 60°C for 45 min, heated and stirred, 12 g of the pretreated basalt fiber was added, and the fiber was soaked for 7 h, washed with deionized water, and dried at 70°C for 12 h to obtain a modified fiber 1.

[0075] S2: Add 6.3 g of silane coupling agent KH-602 to 105 mL of 90 vt% ethanol solution, heat at 60 ° C and stir for 45 min, then add 10.5 g of modified fiber 1, soak for 12 h, filter, wash with anhydrous ethanol, and dry at 80 ° C for 10 h to obtain modified basalt fiber;

[0076] S3: Add 260 mL of diphenyl sulfone to a container, heat to 170°C, then add 36 g of 4,4'-dihydroxybenzophenone, 55 g of 1,4-bis(4-fluorobenzoyl)benzene and 22 g of sodium carbonate in sequence, and heat to react. The reaction process is: first heat to 220°C, maintain for 1 hour, then heat to 320°C, and continue stirring for 3 hours. After the reaction is completed, cool, crush, wash with acetone and distilled water, and vacuum dry at 85°C for 12 hours to obtain a powder;

[0077] S4: 12 g of powder and 32 g of modified basalt fiber are mixed evenly, added into a twin-screw extruder, extruded after melting, and stretched to obtain a central fiber filament.

[0078] This embodiment discloses a method for preparing a composite conductor for bending-resistant medical wire, comprising the following steps:

[0079] Step (1): spraying the prepared composite coating evenly on the surface of the copper wire, and drying to obtain a metal round copper wire;

[0080] Step (2): Wrap the metal round copper wire tightly on the surface of the central fiber wire and compact it to obtain a composite conductor for bending-resistant medical wire with an outer diameter of 0.03 mm and 4 strands.

[0081] Embodiment 5: This embodiment discloses a method for preparing a composite coating, comprising the following steps:

[0082] Q1: 0.055 g 3,8-dibromophenanthroline, 0.13 g sodium carbonate and 0.094 g 4-formylphenylboronic acid were added to a container containing 7 mL N,N-dimethylformamide, and stirred evenly. Then, 5 mL 1,4-dioxane, 0.7 mL ethanol, 0.061 mL methyltrioctylammonium chloride and 0.08 mL tetrakis(triphenylphosphine)palladium were added, and nitrogen was degassed for 45 min. The mixture was heated and stirred at 110°C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, chloroform was added to dissolve the product, and the product was washed with saturated sodium carbonate and distilled water. The organic phase was separated and collected, dried with anhydrous sodium sulfate, filtered and concentrated, and purified with a mixed solution of chloroform and ethyl acetate in a volume ratio of 7:1 as the eluent to obtain intermediate 1;

[0083] Q2: 14.8 mg of intermediate 1, 70 mg of fullerene and 38.67 mg of sarcosine were added to a container, followed by 18 mL of chlorobenzene. The mixture was heated at 120°C for 12 h. After the reaction was completed, it was distilled under reduced pressure and purified using a mixed solution of carbon disulfide and ethyl acetate in a volume ratio of 20:1 as an eluent. After purification, intermediate 2 was obtained. 18 g of intermediate 2 was mixed with 5 g of polyvinyl pyrrolidone and 9 mL of distilled water and stirred for 3 h to obtain a composite coating.

[0084] This embodiment discloses a method for preparing a central fiber, comprising the following steps:

[0085] S1: The basalt fiber was subjected to a heating treatment at 550°C. After the treatment, the fiber was cooled, placed in a 1 mol / L hydrochloric acid solution and heated at 80°C for 6 hours for acid washing, filtered, washed with deionized water until pH = 7, and dried at 80°C for 12 hours to obtain a pretreated basalt fiber. 250 mL of deionized water and 1.8 g of hexadecyltrimethylammonium bromide were mixed at 60°C for 45 minutes, heated and stirred, 18 g of the pretreated basalt fiber was added, and the fiber was soaked for 7 hours, washed with deionized water, and dried at 70°C for 12 hours to obtain a modified fiber 1.

[0086] S2: Add 6.9 g of silane coupling agent KH-602 to 115 mL of 90 vt% ethanol solution, heat to 60 ° C and stir for 45 min, then add 11.5 g of modified fiber 1, soak for 12 h, filter, wash with anhydrous ethanol, and dry at 80 ° C for 10 h to obtain modified basalt fiber;

[0087] S3: Add 320 mL of diphenyl sulfone to a container, heat to 170°C, then add 44 g of 4,4'-dihydroxybenzophenone, 64 g of 1,4-bis(4-fluorobenzoyl)benzene and 27 g of sodium carbonate in sequence, and heat to react. The reaction process is: first heat to 220°C, maintain for 1 hour, then heat to 320°C, and continue stirring for 3 hours. After the reaction is completed, cool, crush, wash with acetone and distilled water, and vacuum dry at 85°C for 12 hours to obtain a powder;

[0088] S4: 18 g of powder and 48 g of modified basalt fiber are mixed evenly, added into a twin-screw extruder, extruded after melting, and stretched to obtain a central fiber filament.

[0089] This embodiment discloses a method for preparing a composite conductor for bending-resistant medical wire, comprising the following steps:

[0090] Step (1): spraying the prepared composite coating evenly on the surface of the copper wire, and drying to obtain a metal round copper wire;

[0091] Step (2): Wrap the metal round copper wire tightly on the surface of the central fiber wire and compact it to obtain a composite conductor for bending-resistant medical wire with an outer diameter of 0.06 mm and 7 strands.

[0092] Comparative Example 1: Compared with Example 1, in the preparation process of the composite coating in Comparative Example 1, no fullerene is added, and other conditions remain unchanged.

[0093] Comparative Example 2: Compared with Example 1, in Comparative Example 2, during the preparation of the central fiber yarn, hexadecyltrimethylammonium bromide was not added, and other conditions remained unchanged.

[0094] Comparative Example 3: Compared with Example 1, in the preparation process of the composite wire in Comparative Example 3, the composite coating is not sprayed, and other conditions remain unchanged.

[0095] Comparative Example 4: Compared with Example 1, in the preparation process of the composite conductor in Comparative Example 4, basalt fiber is used instead of the central fiber, and other conditions remain unchanged.

[0096] The bending resistance of the composite conductor is tested according to GB / T 4909.5-2009, and the corrosion resistance of the composite conductor is tested according to GB / T10125-2021. The corrosion resistance is judged by the mass reduction rate. The mass reduction rate = [(m 前 -m 后 ) / m 前 ]×100% test results are shown in Table 1:

[0097] Table 1

[0098] project Bending times Mass reduction rate / % Example 1 <![CDATA[1.25×10 4 ]]> 4.20 Example 2 <![CDATA[1.24×10 4 ]]> 4.24 Example 3 <![CDATA[1.24×10 4 ]]> 4.29 Example 4 <![CDATA[1.23×10 4 ]]> 4.28 Example 5 <![CDATA[1.23×10 4 ]]> 4.29 Comparative Example 1 <![CDATA[1.23×10 4 ]]> 6.42 Comparative Example 2 <![CDATA[9.91×10 3 ]]> 4.29 Comparative Example 3 <![CDATA[1.23×10 4 ]]> 6.87 Comparative Example 4 <![CDATA[9.8×10 3 ]]> 4.30

[0099] It can be seen from the test results in Table 1 that the composite wires prepared in Examples 1-5 of the present invention have excellent bending resistance and corrosion resistance. Comparison between Comparative Example 1 and Examples 1-5 shows that the addition of fullerene can make the composite wire have excellent corrosion resistance; comparison between Comparative Example 2 and Examples 1-5 shows that the addition of hexadecyltrimethylammonium bromide can make the composite wire have excellent bending resistance; comparison between Comparative Example 3 and Examples 1-5 shows that spraying composite coating can make the composite wire have excellent corrosion resistance; comparison between Comparative Example 4 and Examples 1-5 shows that the use of central fiber can make the composite wire have excellent bending resistance.

[0100] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0101] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A composite conductor for bending-resistant medical wire, characterized in that: The composite conductor is composed of a central fiber and a metal round copper wire, wherein the metal round copper wire is tightly wrapped on the surface of the central fiber, wherein the metal round copper wire is prepared from metal copper wire and a composite coating, and the composite coating is prepared from 3,8-dibromophenanthroline, 4-formylphenylboric acid, fullerene and sarcosine, and the central fiber is prepared from modified basalt fiber, 4,4'-dihydroxybenzophenone and 1,4-bis(4-fluorobenzoyl)benzene; the outer diameter of the composite conductor is 0.02-0.10 mm, and the number of strands is 1-12.

2. The composite conductor for bending-resistant medical electric wire according to claim 1, characterized in that: The preparation method of the composite coating, The following steps are involved: Q1: Add 3,8-dibromophenanthroline, sodium carbonate and 4-formylphenylboronic acid to a container containing N,N-dimethylformamide, stir evenly, then add 1,4-dioxane, ethanol, methyltrioctylammonium chloride and tetrakis(triphenylphosphine)palladium, degas with nitrogen, heat and stir to react, after the reaction is completed, cool to room temperature, add chloroform to dissolve the product, wash, separate and collect the organic phase, dry, filter, concentrate and purify to obtain intermediate 1; Q2: Add intermediate 1, fullerene and sarcosine into a container, then add chlorobenzene and heat to react. After the reaction is completed, perform vacuum distillation and purification to obtain intermediate 2, which is then mixed with polyvinyl pyrrolidone and distilled water to obtain a composite coating.

3. The composite conductor for bending-resistant medical electric wire according to claim 2, characterized in that: In the Q1, the dosage ratio of 3,8-dibromophenanthroline, sodium carbonate, 4-formylphenylboric acid, N,N-dimethylformamide, 1,4-dioxane, ethanol, methyltrioctylammonium chloride and tetrakis(triphenylphosphine)palladium is (0.033-0.066) g: (0.105-0.21) g: (0.051-0.1) g: (4-8) mL: (3-6) mL: (0.4-0.8) mL: (0.033-0.067) mL: (0.05-0.1) mL, the nitrogen degassing time is 30-45 min, the heating and stirring temperature is 110-120° C., the reaction time is 3-5 h, the product is washed with saturated sodium carbonate and distilled water, dried with anhydrous sodium sulfate, and purified using a mixed solution of chloroform and ethyl acetate in a volume ratio of 7:1 as an eluent.

4. The composite conductor for bending-resistant medical electric wire according to claim 2, characterized in that: In the Q2, the amount ratio of intermediate 1, fullerene, sarcosine and chlorobenzene is (8.6-17.3) mg: (40-80) mg: (22-44.84) ​​mg: (10-20) mL, the heating reaction temperature is 110-120°C, the time is 10-12 h, and the purification is carried out using a mixed solution of carbon disulfide and ethyl acetate in a volume ratio of 20:1 as an eluent. The amount ratio of intermediate 2, polyvinyl pyrrolidone and distilled water is (10-20) g: (2-7) g: (8-12) mL, and the mixing and stirring time is 2-4 h.

5. The composite conductor for bending-resistant medical electric wire according to claim 1, characterized in that: The method for preparing the central fiber yarn comprises the following steps: S1: heat-treating the basalt fiber, cooling it after the treatment, heating it in a hydrochloric acid solution for pickling, filtering, washing, and drying it to obtain pretreated basalt fiber, mixing deionized water and hexadecyltrimethylammonium bromide, heating and stirring, adding the pretreated basalt fiber, soaking it, washing it, and drying it to obtain modified fiber 1; S2: adding silane coupling agent KH-602 to the ethanol solution, heating and stirring, then adding modified fiber 1, soaking, filtering, washing, and drying to obtain modified basalt fiber; S3: Add diphenyl sulfone to a container, and then add 4,4'-dihydroxybenzophenone, 1,4-bis(4-fluorobenzoyl)benzene and sodium carbonate in sequence after heating, and heat to react. After the reaction is completed, cool, crush, wash, and vacuum dry to obtain a powder; S4: After the powder and modified basalt fiber are evenly mixed, they are added into a twin-screw extruder, extruded after melting, and stretched to obtain a central fiber filament.

6. The composite conductor for bending-resistant medical electric wire according to claim 5, characterized in that: In S1, the heating treatment temperature is 500-550°C, the concentration of the hydrochloric acid solution is 1 mol / L, the heating pickling temperature is 80-90°C, the time is 5-7h, the fiber is washed with deionized water until pH=7, the drying temperature is 70-80°C, the time is 10-12h, the amount ratio of deionized water, hexadecyltrimethylammonium bromide and pretreated basalt fiber is (150-300)mL: (1-2)g: (10-20)g, the mixing temperature is 60-70°C, the time is 30-45min, the soaking time is 6-8h, the fiber is washed with deionized water, the drying temperature is 70-85°C, and the time is 10-12h.

7. The composite conductor for bending-resistant medical electric wire according to claim 5, characterized in that: In the S2, the volume fraction of the ethanol solution is 90vt%, the amount ratio of the ethanol solution, the silane coupling agent KH-602 and the modified fiber 1 is (100-120)mL: (6-7.2)g: (10-12)g, the heating and stirring temperature is 60-80°C, the time is 30-45min, the soaking time is 10-12h, and the washing is carried out with anhydrous ethanol. The drying temperature is 80-90°C and the time is 10-12h.

8. The composite conductor for bending-resistant medical electric wire according to claim 5, characterized in that: In S3, the dosage ratio of diphenyl sulfone, 4,4'-dihydroxybenzophenone, 1,4-bis(4-fluorobenzoyl)benzene and sodium carbonate is (240-360) mL: (32-48) g: (49-74) g: (19-29) g, the heating temperature is 160-170°C, and the heating reaction process is: first heating to 220°C, maintaining for 1 hour, then heating to 320°C, stirring continuously for 3 hours, washing with acetone and distilled water, and vacuum drying at 80-85°C for 10-12 hours. In S4, the mass ratio of powder to modified basalt fiber is (10-20): (30-50).

9. The method for preparing a composite conductor for bending-resistant medical wire according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step (1): spraying the prepared composite coating evenly on the surface of the copper wire, and drying to obtain a metal round copper wire; Step (2): Wrap the metal round copper wire tightly on the surface of the central fiber wire and compact it to obtain a composite conductor for bending-resistant medical wire with an outer diameter of 0.02 to 0.10 mm and a strand number of 1 to 12.

Citation Information

Patent Citations

  • Medical treatment composite cable

    CN207676687U

  • Method for preparing poly aryl ether ketone copolymers by adopting quaternary copolymerization technique

    CN101580583A

  • Preparation method of multi-purpose coating containing basalt fibers

    CN114836092A

  • Poly(arylene ether ketone) and its production

    JP1991121125A